Service quality and customer satisfaction: a study of restaurants in vavuniya divisional secretariat. - Pushpanathan, A. (Faculty of Business Studies, Vavuniya Campus of the University of Jaffna., 2019)
Service quality is essential to the service supplying organizations, including the restaurants. The restaurateurs should consider more about the quality of their services. Then, they can compete with their competitors successfully. The service quality is a crucial ingredient for every customer. The restaurateurs should give that kind of importance for service quality. Customer is the key person who describes the quality. Restaurateurs should give their services according to the customers' requirements. If customers get quality services from the restaurants, they will come to those restaurants to get their services again. It will help to restaurateurs to improve their customer base, and they can improve their position in the market. The main objective of this study is to identify the relationship and impact of service quality with customer satisfaction of the Restaurant industry in Vavuniya Divisional Secretariat. The five dimensions in SERVQUAL model identified by Parasuraman et al. (1988) were used as independent variables - Tangibility, reliability, responsiveness, assurance, and empathy- and Customer satisfaction is considered as the dependent variable in this study. One hundred customers are randomly selected from the 05 restaurants in Vavuniya Divisional Secretariat, and the data were collected from the selected customers in the restaurants. The data were entered in SPSS 20 package. The correlation and regression analysis were used in the present study. The finding of the present study indicated that the service quality and customer satisfaction has positively correlated, the overall service quality has a high impact on customer satisfaction, and the dimensions of service quality has an association with customer satisfaction.
Keywords: Assurance; Empathy; Responsiveness; Restaurants.; Service quality; Tangibility; Reliability